Positive effects of wood ash fertilization and weed control on the growth of Scots pine on former peat-based agricultural land – a 21-year study - Hytönen, Jyrki; Jylhä, Paula; Little, Keith (Silva Fennica, 2017)
The impacts of weed control, ash fertilization and their interaction were tested for the afforestation of former agricultural peat-based soil with Scots pine ( L.) in northern Finland in a factorial arrangement of four treatments. Weed control with herbicides was carried out in July 1 and 2 years from planting, and wood ash (5 Mg ha) was applied in the spring of the 2nd year. Various vegetation, tree growth and nutrient assessments were made over the 21-year study period. Weed control decreased the weed cover by 36â56 percentage points, vegetation height by 4â26Â cm and thus shading of seedlings by vegetation for at least 4 years after planting. For the same period, ash fertilization increased vegetation height by 6â15 cm and shading of seedlings. Weed control reduced seedling mortality by 27 percentage points in 21 years, but ash fertilization had no significant effect. Ash fertilization increased foliar potassium and boron concentrations, but its effect declined, and severe K-deficiency was recorded 21 years after planting. Up to the 9th year, weed control had a greater influence on growth than fertilization. Later the significance of fertilization increased due to an aggravated K-deficiency. Stand volume at year 21 for the untreated control plots was 8 m ha. Weed control and fertilization increased stand volume by 20 and 35Â m ha, with a combined effect of 55 m ha. The effects of weed control and fertilization were additive and no significant interactions were found. Due to severe K-deficiencies, re-fertilization of all treatments would be necessary for the continued survival and growth of Scots pine.Pinus sylvestrisâ13â13â13â1